2017
DOI: 10.1186/s12884-017-1483-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of oral misoprostol for induction of labour in a resource-limited setting: a dose escalation study

Abstract: BackgroundOral misoprostol as an induction of labour (IOL) agent is rapidly gaining popularity in resource-limited settings because it is cheap, stable at ambient temperatures, and logistically easier to administer compared to dinoprostone and oxytocin. We aim to investigate the safety and effectiveness of a regimen of oral misoprostol in Papua New Guinean women undergoing IOL.MethodsAs part of a prospective dose escalation study conducted at Modilon Hospital in Papua New Guinea, women with a singleton pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
(29 reference statements)
2
17
2
Order By: Relevance
“…6 In this study out of 100 patients 35 required only one dose, 25 required 2 doses and 17 patients required 3 doses, 11 required 4 and 12 patients required 5 doses. In study by Nahar et al, it is showed that out of 60 patients 31(51.7%) patients needed only 1 dose of misoprostol and 24(40%) patients needed 2 doses and only 5(8.3%) patients needed 3 doses of Misoprostol.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…6 In this study out of 100 patients 35 required only one dose, 25 required 2 doses and 17 patients required 3 doses, 11 required 4 and 12 patients required 5 doses. In study by Nahar et al, it is showed that out of 60 patients 31(51.7%) patients needed only 1 dose of misoprostol and 24(40%) patients needed 2 doses and only 5(8.3%) patients needed 3 doses of Misoprostol.…”
Section: Discussionmentioning
confidence: 64%
“…In the study carried out by Marilyn Morris et al on "Safety and effectiveness of oral misoprostol for induction of labour in a resource-limited setting: a dose escalation study" at New Guinea, median age of pregnant women was 27 years. 6 A similar study carried out by Shazia Syed et al have taken 250 pregnant women in age group of 18 to 24 years, among which 47% (118) were primigravida. The mean age with standard deviation of the study population was 24.08±3.25 years with the range of 18 to 31 years in study of Aftabun Nahar et al 7 The most common indication for induction of labour in the present study was postdatism (58%) and PROM was 42%.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations